2009
DOI: 10.1590/s1809-29502009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de vida de pacientes com trauma craniencefálico

Abstract: A percepção de qualidade de vida relacionada à saúde de um paciente com doença crônica, quando avaliada, pode refletir quanto os efeitos de uma doença ou tratamento exercem sobre a vida diária, o nível de satisfação e bem-estar. O objetivo aqui foi avaliar a qualidade de vida de indivíduos com trauma craniencefálico (TCE), por meio do instrumento WHOQOL-bref, e verificar possíveis associações com características sociodemográficas e clínicas dos pacientes. Participaram 120 pacientes com TCE que concluíram um pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
3
1
4
Order By: Relevance
“…Although Silva et al 7 referred to the means of locomotion not having any relation to the QL in their research, the present study saw the majority of patients being physically independent and competent for the personal activities of daily life, something that could have bolstered an improved perception of QL, according to other researchers.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Although Silva et al 7 referred to the means of locomotion not having any relation to the QL in their research, the present study saw the majority of patients being physically independent and competent for the personal activities of daily life, something that could have bolstered an improved perception of QL, according to other researchers.…”
Section: Discussioncontrasting
confidence: 41%
“…5 According to Mendes,6 few individuals after a severe TBI are able to resume their normal activities with independence. In addition, a study by Silva et al 7 points out the effects that a severe TBI can have on the satisfaction and wellbeing of the patient's quality of life (QL). The main findings indicate that educational level and social adjustment were the factors that most influenced the perception of a better QL, while social class and form of locomotion did not show great relationships.…”
mentioning
confidence: 99%
“…As respostas da escala variam de intensidade (nada-extremamente), capacidade (nada-completamente), frequência (nunca-sempre) e avaliação (muito insatisfeito-muito satisfeito e muito ruim-muito bom) (Fleck et al, 1999). O WHOQOL-BREF já foi empregado no Brasil em estudos com idosos (Pereira et al, 2006), pessoas com lesão medular (Bampi, Guilhem e Lima, 2008), com trauma cranioencefálico (Silva et al, 2009), com depressão (Fleck et al, 2002) e portadoras de HIV/Aids (Santos, França Júnior e Lopes, 2007). Também foi utilizado em diversas pesquisas com estudantes universitários (Saupe et al, 2004;Kawakame e Miyadahira, 2005;Catunda e Ruiz, 2008;Hassed et al, 2009;Ramos-Dias et al, 2010;Alves et al, 2010;Leite et al, 2011;Arronqui et al, 2011;Bampi et al, 2013aBampi et al, , 2013b.…”
Section: Métodounclassified
“…In the national literature, two studies using the WHOQOL-BREF to evaluate quality of life in TBI victims, showed an association between the outcomes and the sociodemographic variables of the victims. In one of these (14) the lowest values in the physical domain were associated with females and those of older age, in the other (15) , moderate correlations, though significant, were observed between overall quality of life and educational level (p≤ 0.05) and return to work or study (p≤ 0.01).…”
Section: Rev Esc Enfermmentioning
confidence: 90%